Synovial fibroblasts as target cells for staphylococcal enterotoxin-induced T-cell cytotoxicity - Kraft, Sabrina; Filsinger, Sabine; Krämer, K.-L.; Kabelitz, D.; Hänsch, Gertrud Maria; Schöls, Margarita (Immunology, 1998)
Rheumatoid arthritis (RA) is a chronic autoimmune disease of unknown aetiology. Recently, superantigens have been implied in the pathogenesis of RA. Superantigens activate a large fraction of T cells leading to the production of cytokines and proliferation. In addition, superantigens direct cellular cytotoxicity towards major histocompatibility complex (MHC) class II-expressing cells. There is now increasing evidence that cytotoxic T cells may be involved in the pathogenesis of RA. In the inflamed synovia class II-positive synovial fibroblasts (SFC) are found. In the present study it was tested whether MHC class II-positive SFC serve as target cells for superantigen-induced cellular cytotoxicity. SFC were stimulated with interferon-γ to express class II antigens, then they were cultivated in the presence of CD4-positive T cells with or without staphylococcal enterotoxins (SE). Cytotoxicity of T cells was measured as release of lactate dehydrogenase from SFC. Specific cytotoxicity was only found in the presence of class II-positive SFC depending on the dose of SE. Maximum lysis was seen after 20 hr. T-cell cytotoxicity was inhibited by antibodies to MHC class II antigens. The data suggest that class II-positive SFC not only function as accessory cells for SE-mediated T-cell proliferation and interleukin-2 production but may also be the targets of superantigen-mediated cellular cytotoxicity.
Elektronische Reproduktion der Druck-Ausgabe 24. September 2008
Gesehen am 05.06.2025